Research on Heading Statically Unstable Aircraft Control Method Based on Improved LQR - WEI Mingjun; WANG Changqing; XU Cheng (Kongzhi Yu Xinxi Jishu)
Aiming at the characteristics of strong coupling between lateral and heading of heading statically unstable aircraft, the control method of lateral and heading stabilization was studied in this paper. Firstly, a lateral-heading coupling mathematical model of the course-statically unstable aircraft was established. Then, aiming at the steady-state error of the conventional LQR controller and the difficulty of measuring the sideslip angle, a quasi-augmented LQR method was used to design the lateral-heading stabilization control loop. Finally, the trajectory simulation of the aircraft tracking under different commands was carried out. Simulation results show that the method of stabilization loop design in this paper can make the course statically unstable aircraft achieve no static error tracking of input commands, and the response process is not overshoot, and the adjustment time is short.